Pseudopilin residue E5 is essential for recruitment by the type 2 secretion system assembly platform. Issue 6 (5th July 2016) - Nivaskumar, Mangayarkarasi; Santos‐Moreno, Javier; Malosse, Christian; Nadeau, Nathalie; Chamot‐Rooke, Julia; Tran Van Nhieu, Guy; Francetic, Olivera
Summary: Type II secretion systems (T2SSs) promote secretion of folded proteins playing important roles in nutrient acquisition, adaptation and virulence of Gram‐negative bacteria. Protein secretion is associated with the assembly of type 4 pilus (T4P)‐like fibres called pseudopili. Initially membrane embedded, pseudopilin and T4 pilin subunits share conserved transmembrane segments containing an invariant Glu residue at the fifth position, E5. Mutations of E5 in major T4 pilins and in PulG, the major pseudopilin of the Klebsiella T2SS abolish fibre assembly and function. Among the four minor pseudopilins, only PulH required E5 for secretion of pullulanase, the substrate of the Pul T2SS. Mass‐spectrometry analysis of pili resulting from the co‐assembly of PulG E5A variant and PulG WT ruled out an E5 role in pilin processing and N‐methylation. A bacterial two‐hybrid analysis revealed interactions of the full‐length pseudopilins PulG and PulH with the PulJ‐PulI‐PulK priming complex and with the assembly factors PulM and PulF. Remarkably, PulG E5A and PulH E5A variants were defective in interaction with PulM but not with PulF, and co‐purification experiments confirmed the E5‐dependent interaction between native PulM and PulG. These results reveal the role of E5 in a recruitment step critical for assembly of the functional T2SS, likely relevant to T4P assembly systems. Abstract : The highly conserved Glu residue at position 5 (E5) in the transmembrane segments of T2SS pseudopilins and type 4 pilins is essential for fibre assembly and function. Using the bacterial two‐hybrid and copurification approaches, we show that the major T2SS pseudopilin and one of four minor pseudopilins interact with the assembly platform components PulM and PulF. Residue E5 is specifically required for interactions with PulM, suggesting a role in pseudopilin recruitment to the assembly complex.